Knowledge and exercise of human rights, and barriers and facilitators to claiming rights: a cross-sectional study of female sex workers and high-risk men who have sex with men in Andhra Pradesh, India. Issue 1 (December 2016) - Ganju, Deepika; Patel, Sangram; Prabhakar, Parimi; Adhikary, Rajatashurva
Abstract Background HIV prevention interventions recognize the need to protect the rights of key populations and support them to claim their rights as a vulnerability reduction strategy. This study explores knowledge of human rights, and barriers and facilitators to claiming rights, among female sex workers (FSWs) and high-risk men who have sex with men (HR-MSM) who are beneficiaries of a community mobilization intervention in Andhra Pradesh, India. Methods Data are drawn from a cross-sectional survey (2014) among 2400 FSWs and 1200 HR-MSM. Human rights awareness was assessed by asking respondents if they had heard of human rights (yes/no); those reporting awareness of rights were asked to spontaneously name specific rights from the following five pre-defined categories: right to health; dignity/equality; education; property; and freedom from discrimination. Respondents were classified into two groups: more knowledgeable (could identify two or more rights) and less knowledgeable (could identify one or no right). Univariate and bivariate analyses and chi-square tests were used. Data were analyzed using STATA 11.2. Results Overall 17% FSWs and 8% HR-MSM were not aware of their rights. Among those aware, 62% and 31% respectively were aware of just one or no right (less knowledgeable); only around half (54% vs 57%) were aware of health rights, and fewer (20% vs 16%) aware of their right to freedom from discrimination. Notably, 27% and 17% respectively had not exercised their rights. Barriers to claiming rights among FSWs and HR-MSM were neighbors (35% vs 37%), lack of knowledge (15% vs 14%), stigma (13% vs 22%) and spouse (19% FSWs). Community organizations (COs) were by far the leading facilitator in claiming rights (57% vs 72%). Conclusions The study findings show that awareness of human rights is limited among FSWs and HR-MSM, and a large proportion have not claimed their rights, elevating their HIV vulnerability. For a sustained HIV response, community mobilization efforts must focus on building key populations' awareness of rights, and addressing the multiple barriers to claiming rights, with a view to creating a safe environment where vulnerable groups can demand and use services without fear of stigma, discrimination and violation of rights.